(3GdLhGfH GdbGfhfjI ddJOGhd GdEdcJQhfi ddChQGb GdeGdjI (B: s (3OQGSI ebGQfI (B/ s - (3OjfG EHQGgje eMeO jhSa GdaGQs; (3Ndjd ajcJhQ JGOQSs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2016)
(3Ef fXGe GdJOGhd GdEdcJQhfi ddChQGb GdeGdjI jJjM ddeSJKeQ EOGQI GSJKeGQGJg ai GdChQGb GdeGdjI h eTJbGJgG ef NdGd THcI GdeYdheGJ GdOhdjI (B((3GdEfJQfJ(B) (3ShGA HGdHjY Ch GdTQGA Ch ef NdGd bjGeg HJfajP ChGeQ GdeJGHYI GdJi jbhe HEUOGQgG GdcQJhfjG ef NdGd ehbY GdEfJQfJ GdNGU HTQcI GdSeSQI GdeGdjI GdJi jJYGed eYgG h GdeQNU dgG HJbOje NOeI GdJOGhd GdEdcJQhfi ddChQGb GdeGdjI(B: (3h HGdJGdi agh fXGe eYdheGJi jSJfO Edi bGYOI HjGfGJ h ef Gdeecf Cf jJYQV dCi eNGWQ ShGA HGdEJdGa HUhQI eHGTQI Ch ZjQ eHGTQI(B: (3dPdc aef GdVQhQi GdYed Ydi MeGjI GdehGbY GdEdcJQhfjI dJdc GdfXe h Pdc dJMbjb eUGdM GdCWQGa GdeJYGedI HgPg GdfXe h dci jchf gfGc bOQ ef GdVeGfGJ GdbGfhfjI GdcajdI HMeGjJge(B.s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdJLGQj (B2016.s
(3HHdjhLQGajG(B: (3UaMGJ (B521-554.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdHhQUGJ GdEdcJQhfjIs; (3GdChQGb GdeGdjIs; (3GdJhbjY GdEdcJQhfjs; (3GdYbO GdEdcJQhfjs; (3GdJOGhd GdEdcJQhfjs; (3Uchc GdJehjds; (3YbhO GdNjGQGJs; (3TQcGJ GdSeSQI GdeGdjIs; (3CShGb GdeGd GdYQHjIs; (3CShGb GdeGd GdCLfHjIs; (3LOGhd GdHhQUIs; (3HhQUI GdChQGb GdeGdjIs; (3GdSfOGJs; (3GdCSges; (3GdCShGb GdeGdjIs; (3TgGOGJ GdEjOGY GdOhdjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs